2002
DOI: 10.1029/2001gl013912
|View full text |Cite
|
Sign up to set email alerts
|

Hydroacoustic monitoring of seismicity at the slow‐spreading Mid‐Atlantic Ridge

Abstract: In February 1999, long‐term hydroacoustic monitoring of the northern Mid‐Atlantic Ridge (MAR) was initiated. Six autonomous hydrophones were moored between ∼15°N and ∼35°N on the flanks of the MAR. Results from the first year of data reveal that there is significant variability in along‐axis event rate. Groups of neighboring segments behave similarly, producing an along‐axis pattern with high and low levels of seismic activity at a wavelength of ∼500 km. This broad scale pattern is likely influenced by the axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 17 publications
5
82
0
Order By: Relevance
“…The remaining sections of the ridge axis were unclassified. Seismicity data were obtained from the hydrophone catalog 11 and from the NEIC teleseismic catalog (http://neic.usgs.gov/). So as to remove intraplate seismicity and that associated with off-axis deformation, we restricted our analysis to events in oceanic lithosphere younger than 3 Myr, based on the digital seafloor age map 29 .…”
Section: Methods Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining sections of the ridge axis were unclassified. Seismicity data were obtained from the hydrophone catalog 11 and from the NEIC teleseismic catalog (http://neic.usgs.gov/). So as to remove intraplate seismicity and that associated with off-axis deformation, we restricted our analysis to events in oceanic lithosphere younger than 3 Myr, based on the digital seafloor age map 29 .…”
Section: Methods Summarymentioning
confidence: 99%
“…The remaining ~20% of the axis is unclassified owing to limited bathymetric coverage or to unclear morphology at discontinuities and oblique ridge sections (see interpreted maps and Table 1 There is an excellent correlation between mode of accretion and seismicity at the ridge axis. This section of the MAR was hydroacoustically monitored between January 1999 and September 2003 11 . The hydroacoustic catalogue is complementary to the >30 year teleseismic catalogue, as it records smaller magnitude events (magnitude of completeness of 3 and 5, respectively 12 ), over a shorter period of time (<5 vs. >30 years).…”
mentioning
confidence: 99%
“…Between 1999-2005 an autonomous hydrophone array in the North Atlantic 22 recorded the hydroacoustic energy from thousands of earthquakes of smaller magnitude (>2.5). Hydroacoustic events are better located than those detected teleseismically 22,23 , and clearly show the currently active sections of MAR segments 16 . Two sections of ridge between the Fifteen-Twenty and Marathon fracture zones (Fig.…”
mentioning
confidence: 99%
“…The scientific contributions of hydroacoustic studies have been numerous. For example, they have revolutionized our understanding of mid-ocean ridge eruptive processes (e.g., Fox et al, 1995;Dziak and Fox, 1999), illuminated the impact of submarine earthquakes on hydrothermal systems (e.g., Johnson et al, 2000;Dziak et al, 2003), addressed a wide variety of tectonic problems (e.g., Smith et al, 2002;Bohnenstiehl et al, 2002Bohnenstiehl et al, , 2004Dziak, 2006), and recently demonstrated the predictability of earthquakes on oceanic transform faults (McGuire et al, 2005). Because the Navy does not archive the SOSUS records, the near continuous 20-year library of North Pacific SOSUS digital data collected by NOAA/OSU represents a globally unique earthquake and ocean acoustic data set.…”
mentioning
confidence: 99%